Sunshade net with self-cleaning function and preparation method thereof
By designing a nano-level concave-convex structure and multi-layer coating synergistically on the shade net, combined with fluorocarbon polymers and nano titanium dioxide photocatalysts, the shade net achieves high-efficiency self-cleaning and multiple functions, solving the problems of dust accumulation and insufficient coating adhesion in traditional shade nets used outdoors, and improving service life and environmental benefits.
Patent Information
- Application Number
- CN202411375881.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-07
AI Technical Summary
Traditional shade nets tend to accumulate dust and dirt during outdoor use, have limited self-cleaning properties, insufficient coating adhesion, and limited functionality, making it difficult to meet diverse needs.
The surface of the polyethylene fiber substrate is designed with a nanoscale concave-convex structure, combined with a fluorocarbon polymer layer and a nano titanium dioxide photocatalyst. Through the synergistic effect of multiple coatings, including a superhydrophobic coating and a self-assembled monolayer film, the self-cleaning function is achieved by utilizing photocatalytic activity and superhydrophobicity.
It achieves multiple functions such as efficient self-cleaning, antibacterial and anti-fouling of shade nets, improves the coating's firmness and durability, adapts to outdoor environments, reduces the frequency of manual cleaning, and saves resources.
Smart Images

Figure CN119265950A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sunshade materials, and in particular to a sunshade net with a self-cleaning function and a preparation method thereof. Background Art
[0002] In modern agriculture, gardening and outdoor leisure, sunshade nets are widely used as an important tool for sunshade, cooling and dust prevention. However, traditional sunshade nets are easily exposed to the outdoor environment during use, which not only affects their sunshade effect and aesthetics, but also may become a breeding ground for germs and insects, posing a potential threat to crops and human health. Therefore, the development of sunshade nets with self-cleaning functions has become an important research direction.
[0003] Deficiencies in the prior art:
[0004] Difficult to clean and maintain: Traditional sunshade nets need to be cleaned manually regularly, which is not only time-consuming and labor-intensive, but may also cause damage to the sunshade net due to improper cleaning, increasing the cost of use.
[0005] Limited self-cleaning effect: Some sunshade nets on the market that claim to have self-cleaning functions often only rely on simple hydrophobic coatings or photocatalytic materials, and have limited self-cleaning effects, which are difficult to meet the needs of long-term use.
[0006] Insufficient coating firmness: After some sunshade nets are coated with self-cleaning coating, the bonding force between the coating and the substrate is not strong, which may cause the coating to fall off and crack, thus affecting the service life.
[0007] Single function: Traditional sunshade nets often only focus on the sunshade effect, ignoring other functions such as dustproof, antibacterial, and insect-proof, making it difficult to meet diversified needs.
[0008] Therefore, we propose a sunshade net with self-cleaning function and a preparation method thereof to solve the above problems. Summary of the invention
[0009] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a sunshade net with a self-cleaning function and a preparation method thereof.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] A sunshade net with a self-cleaning function comprises the following components in parts by weight: 40-60 parts of a polyethylene fiber substrate, 3-7 parts of a fluorocarbon polymer layer, 8-12 parts of a resin layer, 2-4 parts of a nano titanium dioxide photocatalyst, 0.5-1.5 parts of a photocatalyst auxiliary component, 3-7 parts of a super-hydrophobic coating, 0.3-0.7 parts of a self-assembled monolayer film, and 1.5-2.5 parts of a cross-linking agent.
[0012] As the preferred technical solution:
[0013] The sunshade net with self-cleaning function as described above includes the following components in parts by weight: 50 parts of polyethylene fiber substrate, 6 parts of fluorocarbon polymer layer, 9 parts of resin layer, 4 parts of nano titanium dioxide photocatalyst, 0.8 parts of photocatalyst auxiliary component, 5 parts of superhydrophobic coating, 0.6 parts of self-assembled monolayer film, and 1.9 parts of cross-linking agent.
[0014] As described above, a sunshade net with a self-cleaning function, the fiber diameter of the polyethylene fiber substrate is 0.2mm~0.5mm, the surface of the polyethylene fiber substrate is subjected to corona treatment or plasma treatment, the fluorocarbon polymer layer uses polyvinylidene fluoride (PVDF) as the main fluorocarbon polymer component, the thickness is 5μm~15μm, the fluorocarbon polymer layer has a micro-nanoscale rough structure, the superhydrophobic coating is composed of fluorosilane and silicon dioxide with a rough structure, the resin layer uses modified silicone resin, the thickness is 3μm~8μm, the resin layer serves as an intermediate layer, connecting the substrate and the functional coating, the self-assembled monolayer film uses molecules with carboxyl groups, and forms an ordered monolayer film on the surface of the substrate through self-assembly technology, the thickness of the self-assembled monolayer film is 1nm~5nm, and the cross-linking agent is an epoxy resin cross-linking agent.
[0015] The sunshade net with self-cleaning function as described above, the nano titanium dioxide photocatalyst adopts anatase nano titanium dioxide, the particle size is 10nm ~ 30nm, the contact angle of the nano titanium dioxide photocatalyst with water is greater than 150°, the rolling angle is less than 10°, and it is prepared by sol-gel method; the photocatalyst auxiliary components include sodium citrate and sodium acetate, the molar ratio of sodium citrate to soluble zinc salt is 1:10 ~ 3:20, and the molar ratio of sodium acetate to soluble zinc salt is 25:10 ~ 40:20.
[0016] As described above, a sunshade net with a self-cleaning function is characterized in that the surface of the polyethylene fiber substrate is designed with a nano-level concave-convex structure, which helps to form a super-hydrophobic surface. When rain falls on the sunshade net, it can quickly form water droplets and roll down, taking away dust and dirt on the surface, and / or the surface of the polyethylene fiber substrate is designed to simulate the wax layer and papillary structure of the self-cleaning surface of the lotus leaf surface; the fluorocarbon polymer is combined with super-hydrophobic nanoparticles to form a nano-composite coating, which not only has the low surface energy characteristics of the fluorocarbon polymer, but also enhances the super-hydrophobicity through the rough structure of the nanoparticles; a chemical method is used to form an ordered self-assembled monolayer film on the surface of the fluorocarbon polymer layer, and the self-assembled monolayer film can adjust the surface energy and improve the binding force with the nanoparticles; the nano-titanium dioxide photocatalyst uses a one-dimensional or two-dimensional titanium dioxide nanostructure as a photocatalyst, and the titanium dioxide is doped and modified by adding nitrogen and sulfur elements to broaden its light absorption range and improve its photocatalytic activity under visible light.
[0017] The second aspect of the present invention provides a method for preparing a sunshade net with a self-cleaning function, comprising the following steps:
[0018] S1: Select polyethylene fiber as the substrate, roughen the fiber surface, and use low-temperature plasma technology to etch micron to nanometer-level concave-convex structures on the fiber surface by adjusting the gas composition and treatment time;
[0019] S2: A thin layer of silane coupling agent is deposited on the roughened surface of the polyethylene fiber substrate by chemical vapor deposition. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the polyethylene fiber to form a covalent bond, and the other end carries a reactive functional group, providing an active site for the firm bonding of the subsequent coating.
[0020] S3: A layer of fluorocarbon polymer solution is uniformly coated on the functionalized fiber surface by solution dipping method;
[0021] S4: depositing a resin layer on the fluorocarbon polymer layer using an electrostatic spraying technique;
[0022] S5: Nano-titanium dioxide particles are synthesized by sol-gel method and uniformly dispersed in aqueous solvent by ultrasonic dispersion technology. Subsequently, the nano-titanium dioxide sol is coated on the resin layer by spin coating. During the spin coating process, the distribution density and uniformity of the nano-particles on the fiber surface are controlled by adjusting the rotation speed and time. Finally, heat treatment is performed at high temperature to make the nano-titanium dioxide particles firmly bonded to the fiber surface and form a crystal structure with high photocatalytic activity.
[0023] S6: On top of the nano-titanium dioxide photocatalyst layer, a super-hydrophobic coating is constructed. First, a layer of low surface energy material is modified on the surface of the nano-titanium dioxide, and then a dense self-assembled monolayer film is formed on its surface by self-assembly technology;
[0024] S7: adding a cross-linking agent, which forms covalent bonds or ionic bonds between the coatings through chemical reactions, thereby firmly locking the entire coating system together;
[0025] S8: After all the above coatings are constructed, the sunshade net is fully cleaned and dried to obtain a sunshade net with a self-cleaning function.
[0026] As the preferred technical solution:
[0027] As described above, a method for preparing a sunshade net with a self-cleaning function, in said S1, polyethylene fiber is selected as a substrate, the fiber surface is roughened, and low-temperature plasma technology is used. The gas composition is a mixture of argon and oxygen, and the ratio is Ar:O2=4:1. The processing time is 30 to 60 seconds, and the power is set to 100 to 200W to etch a micron to nanometer level concave-convex structure on the fiber surface.
[0028] As described above, a sunshade net with a self-cleaning function and a preparation method thereof, in S1, the concave-convex structure is designed to be corrugated, and on the basis of the concave-convex structure, a papillary structure similar to the surface of a lotus leaf is formed on the fiber surface by chemical etching or physical deposition methods.
[0029] As described above, a sunshade net with a self-cleaning function and a preparation method thereof, in said S5, nano titanium dioxide particles are synthesized by a sol-gel method, and are uniformly dispersed in an aqueous solvent by ultrasonic dispersion technology, the concentration of the nano titanium dioxide particles is adjusted to 1% to 3%, and the ultrasonic dispersion time is 30 to 60 minutes, and then the nano titanium dioxide sol is coated on the resin layer by spin coating, the spin coating speed is set to 500 to 1000 rpm, the spin coating time is 30 to 60 seconds, and the distribution density and uniformity of the nano particles on the fiber surface are controlled, and finally, heat treatment is performed at a high temperature to make the nano titanium dioxide particles firmly bonded to the fiber surface, the heat treatment temperature is 400 to 500°C, the duration is 1 to 2 hours, and a crystal structure with high photocatalytic activity is formed.
[0030] As described above, a sunshade net with a self-cleaning function and a preparation method thereof, in said S6, a super hydrophobic coating is constructed on the nano titanium dioxide photocatalyst layer, first, a layer of low surface energy material is modified on the surface of the nano titanium dioxide, the low surface energy material is fluorosilane, and the concentration of the fluorosilane solution is 0.1% to 0.5%, and then a dense self-assembled monolayer film is formed on its surface by self-assembly technology, the self-assembly time is 1 to 2 hours, and the temperature is controlled at 20 to 30°C.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The synergy between the fluorocarbon polymer layer and the super-hydrophobic coating: The fluorocarbon polymer layer provides low surface energy, making it difficult for water and other liquids to adhere to its surface, while the super-hydrophobic coating further enhances this effect by forming a micro-nano rough structure, so that water droplets can quickly form beads and roll off when they come into contact with the surface of the sunshade net, taking away dust and dirt on the surface. This synergy greatly improves the self-cleaning ability of the sunshade net.
[0033] Synergy between nano-titanium dioxide photocatalyst and other coatings: Nano-titanium dioxide photocatalyst has photocatalytic activity under visible light, which can decompose organic matter and kill bacteria, thus keeping the surface of the sunshade net clean. This photocatalytic activity and the synergy of other coatings make the sunshade net not only have self-cleaning ability, but also have multiple functions such as antibacterial and antifouling.
[0034] Synergy between polyethylene fiber substrate and surface structure: The polyethylene fiber substrate has good mechanical properties and durability, and the nano-scale concave-convex structure formed on its surface after corona treatment or plasma treatment helps to form a super-hydrophobic surface and improve the self-cleaning effect. The synergy between this material and structure enables the sunshade net to have excellent self-cleaning performance while maintaining high strength.
[0035] The synergy of cross-linking agent and multi-layer coating: The use of cross-linking agent forms a strong chemical bond or ionic bond between each layer of coating, thereby tightly locking the entire coating system together. This synergy not only improves the firmness and durability of the coating, but also ensures that the sunshade net will not have problems such as peeling or cracking during use.
[0036] Synergy between self-cleaning function and outdoor environment: Sunshade nets are usually used in outdoor environments and are easily affected by natural factors such as dust, rain, and ultraviolet rays. Sunshade nets with self-cleaning function can effectively reduce the pollution and damage caused by these factors on their surface, thereby maintaining their good appearance and performance. This synergy makes the sunshade net have a longer service life and better use effect in outdoor environments.
[0037] Synergy between photocatalyst and ultraviolet light: Nano-titanium dioxide photocatalyst can exert the best photocatalytic activity under the irradiation of ultraviolet light. This synergy enables the sunshade net to more effectively use sunlight energy for self-cleaning and antibacterial treatment in outdoor environments, thereby improving its overall performance and environmental benefits.
[0038] In summary, the self-cleaning sunshade net achieves multiple functions such as efficient self-cleaning, anti-bacteria, and anti-fouling through the synergistic effect of multi-layer coatings, the synergistic effect of materials and structures, and the synergistic effect of environmental adaptability, and improves its overall performance and environmental benefits. These synergies provide strong support for the application of sunshade nets in agriculture, gardening, outdoor leisure and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a surface structure diagram of embodiment 4 of the present invention. DETAILED DESCRIPTION
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."
[0041] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0042] A sunshade net with a self-cleaning function comprises the following components in parts by weight: 40-60 parts of a polyethylene fiber substrate, 3-7 parts of a fluorocarbon polymer layer, 8-12 parts of a resin layer, 2-4 parts of a nano titanium dioxide photocatalyst, 0.5-1.5 parts of a photocatalyst auxiliary component, 3-7 parts of a super-hydrophobic coating, 0.3-0.7 parts of a self-assembled monolayer film, and 1.5-2.5 parts of a cross-linking agent.
[0043] Among them, the fiber diameter of the polyethylene fiber substrate is 0.2mm~0.5mm, the surface of the polyethylene fiber substrate is corona treated or plasma treated, the fluorocarbon polymer layer uses polyvinylidene fluoride (PVDF) as the main fluorocarbon polymer component, the thickness is 5μm~15μm, the fluorocarbon polymer layer has a micro-nano rough structure, the super hydrophobic coating is composed of fluorosilane and silicon dioxide with a rough structure, the resin layer uses modified silicone resin, the thickness is 3μm~8μm, the resin layer is used as an intermediate layer to connect the substrate and the functional coating, the self-assembled monolayer membrane uses molecules with carboxyl groups, and forms an ordered monolayer membrane on the surface of the substrate through self-assembly technology, the thickness of the self-assembled monolayer membrane is 1nm~5nm, and the cross-linking agent is an epoxy resin cross-linking agent.
[0044] The nano titanium dioxide photocatalyst adopts anatase nano titanium dioxide with a particle size of 10nm to 30nm. The contact angle of the nano titanium dioxide photocatalyst with water is greater than 150°, and the rolling angle is less than 10°. It is prepared by a sol-gel method. The photocatalyst auxiliary components include sodium citrate and sodium acetate. The molar ratio of sodium citrate to soluble zinc salt is 1:10 to 3:20, and the molar ratio of sodium acetate to soluble zinc salt is 25:10 to 40:20.
[0045] The surface of the polyethylene fiber substrate is designed with a nano-level concavo-convex structure, which helps to form a super-hydrophobic surface. When rain falls on the sunshade net, it can quickly form water droplets and roll off, taking away dust and dirt on the surface, and / or the surface of the polyethylene fiber substrate is designed to simulate the wax layer and papillary structure of the lotus leaf surface to form a micro-nano structure of a self-cleaning surface;
[0046] The fluorocarbon polymer is combined with nanoparticles having super hydrophobicity to form a nanocomposite coating, which not only has the low surface energy characteristics of the fluorocarbon polymer, but also has enhanced super hydrophobicity due to the rough structure of the nanoparticles;
[0047] An ordered self-assembled monolayer is formed on the surface of the fluorocarbon polymer layer by chemical methods. The self-assembled monolayer can adjust the surface energy and improve the binding force with nanoparticles.
[0048] The nano titanium dioxide photocatalyst uses a one-dimensional or two-dimensional titanium dioxide nanostructure as a photocatalyst, and the titanium dioxide is doped and modified by adding nitrogen and sulfur elements to broaden its light absorption range and improve its photocatalytic activity under visible light.
[0049] Embodiment 1
[0050] A sunshade net with a self-cleaning function comprises the following components in parts by weight: 40 parts of a polyethylene fiber substrate (Hangzhou Quanli Technology Co., Ltd.), 3 parts of a fluorocarbon polymer layer (polyvinylidene fluoride, Dongguan Xinxionghua Plastic Material Co., Ltd.), 8 parts of a resin layer (modified silicone resin, Guangzhou Wanhua New Material Technology Co., Ltd.), 2 parts of a nano-titanium dioxide photocatalyst (Zhejiang Zhiti Nano Micro New Materials Co., Ltd.), 0.5 parts of a photocatalyst auxiliary component (sodium citrate and sodium acetate), 3 parts of a super-hydrophobic coating (composed of fluorosilane and silicon dioxide with a rough structure, Shanghai Kaiyin Chemical Co., Ltd.), 0.3 parts of a self-assembled monolayer film (a molecule with a carboxyl group), and 1.5 parts of a crosslinking agent (an epoxy resin crosslinking agent, Shanghai Kaiyin Chemical Co., Ltd.).
[0051] The embodiment also provides a method for preparing a sunshade net with a self-cleaning function, comprising the following steps:
[0052] S1: Select polyethylene fiber as the substrate, roughen the fiber surface, use low-temperature plasma technology, the gas composition is argon and oxygen mixed, the ratio is Ar: O2 = 4: 1, the processing time is 30 seconds, the power is set to 100W, and the micron to nanometer level concave-convex structure is etched on the fiber surface;
[0053] S2: A thin layer of silane coupling agent is deposited on the roughened surface of the polyethylene fiber substrate by chemical vapor deposition. The deposition temperature is set to 80°C, the deposition time is 10 minutes, and the concentration of the silane coupling agent is controlled at 5%. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the polyethylene fiber to form a covalent bond, and the other end has a reactive functional group, which provides an active site for the firm bonding of the subsequent coating.
[0054] S3: On the surface of the functionalized fiber, a layer of fluorocarbon polymer solution is evenly coated by solution dipping method. The concentration of the fluorocarbon polymer solution is 2%. The dipping time is 3 minutes, and then it is dried at 80°C for 10 minutes to ensure that the coating is uniform and firm.
[0055] S4: On the fluorocarbon polymer layer, a resin layer is deposited by electrostatic spraying technology. The viscosity of the resin solution is adjusted to 50 mPa·s, the spraying voltage is set to 30 kV, the spraying distance is maintained at 10 cm, and after deposition, it is cured at 120°C for 15 minutes;
[0056] S5: Nano-titanium dioxide particles were synthesized by sol-gel method and uniformly dispersed in aqueous solvent by ultrasonic dispersion technology. The concentration of nano-titanium dioxide particles was adjusted to 1% and the ultrasonic dispersion time was 30 minutes. Subsequently, the nano-titanium dioxide sol was coated on the resin layer by spin coating. The spin coating speed was set to 500 rpm and the spin coating time was 30 seconds. The distribution density and uniformity of the nano-particles on the fiber surface were controlled. Finally, heat treatment was performed at high temperature to make the nano-titanium dioxide particles firmly bonded to the fiber surface. The heat treatment temperature was 400°C and the duration was 1 hour. A crystal structure with high photocatalytic activity was formed.
[0057] S6: On the nano-titanium dioxide photocatalyst layer, a super-hydrophobic coating is constructed. First, a layer of low surface energy material is modified on the surface of the nano-titanium dioxide. The low surface energy material is fluorosilane. The concentration of the fluorosilane solution is 0.1%. Then, a dense self-assembled monolayer film is formed on the surface by self-assembly technology. The self-assembly time is 1 hour and the temperature is controlled at 20°C.
[0058] S7: adding a cross-linking agent, which forms covalent bonds or ionic bonds between the coatings through chemical reactions. The concentration of the cross-linking agent is controlled at 1%, the reaction temperature is set at 50°C, and the reaction time is 2 hours, thereby firmly locking the entire coating system together;
[0059] S8: After completing all the above coating construction, dry it naturally at room temperature or use an oven to dry it at 60°C for 30 minutes to ensure that the sunshade net is completely dry and has no residue, thereby obtaining a sunshade net with a self-cleaning function.
[0060] Embodiment 2
[0061] A sunshade net with a self-cleaning function comprises the following components in parts by weight: 45 parts of a polyethylene fiber substrate, 4 parts of a fluorocarbon polymer layer, 9 parts of a resin layer, 3 parts of a nano-titanium dioxide photocatalyst, 0.8 parts of a photocatalyst auxiliary component, 4 parts of a super-hydrophobic coating, 0.4 parts of a self-assembled monolayer film, and 1.7 parts of a cross-linking agent.
[0062] The embodiment also provides a method for preparing a sunshade net with a self-cleaning function, comprising the following steps:
[0063] S1: Select polyethylene fiber as the substrate, roughen the fiber surface, use low-temperature plasma technology, the gas composition is argon and oxygen mixed, the ratio is Ar: O2 = 4: 1, the processing time is 40 seconds, the power is set to 120W, and the micron to nanometer level concave and convex structure is etched on the fiber surface;
[0064] S2: A thin layer of silane coupling agent is deposited on the roughened surface of the polyethylene fiber substrate by chemical vapor deposition. The deposition temperature is set at 90°C, the deposition time is 12 minutes, and the concentration of the silane coupling agent is controlled at 6%. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the polyethylene fiber to form a covalent bond, and the other end has a reactive functional group, which provides an active site for the firm bonding of the subsequent coating.
[0065] S3: A layer of fluorocarbon polymer solution is evenly coated on the surface of the functionalized fiber by solution dipping method. The concentration of the fluorocarbon polymer solution is 3%. The dipping time is 4 minutes, and then it is dried at 85°C for 12 minutes to ensure that the coating is uniform and firm.
[0066] S4: On the fluorocarbon polymer layer, a resin layer was deposited by electrostatic spraying technology. The viscosity of the resin solution was adjusted to 60 mPa·s, the spraying voltage was set to 35 kV, the spraying distance was maintained at 13 cm, and after deposition, it was cured at 130°C for 17 minutes;
[0067] S5: Nano-titanium dioxide particles were synthesized by sol-gel method and uniformly dispersed in aqueous solvent by ultrasonic dispersion technology. The concentration of nano-titanium dioxide particles was adjusted to 2% and the ultrasonic dispersion time was 35 minutes. Subsequently, the nano-titanium dioxide sol was coated on the resin layer by spin coating. The spin coating speed was set to 700 rpm and the spin coating time was 40 seconds. The distribution density and uniformity of the nano-particles on the fiber surface were controlled. Finally, heat treatment was performed at high temperature to make the nano-titanium dioxide particles firmly bonded to the fiber surface. The heat treatment temperature was 430°C and the duration was 1 hour. A crystal structure with high photocatalytic activity was formed.
[0068] S6: On the nano-titanium dioxide photocatalyst layer, a super-hydrophobic coating is constructed. First, a layer of low surface energy material is modified on the surface of the nano-titanium dioxide. The low surface energy material is fluorosilane. The concentration of the fluorosilane solution is 0.2%. Then, a dense self-assembled monolayer film is formed on the surface by self-assembly technology. The self-assembly time is 1 hour, and the temperature is controlled at 25°C.
[0069] S7: adding a cross-linking agent, which forms covalent bonds or ionic bonds between the coatings through chemical reactions. The concentration of the cross-linking agent is controlled at 2%, the reaction temperature is set at 55°C, and the reaction time is 3 hours, thereby firmly locking the entire coating system together;
[0070] S8: After completing all the above coating construction, dry it naturally at room temperature or use an oven to dry it at 65°C for 35 minutes to ensure that the sunshade net is completely dry and has no residue, thereby obtaining a sunshade net with a self-cleaning function.
[0071] Embodiment 3
[0072] A sunshade net with a self-cleaning function comprises the following components in parts by weight: 55 parts of a polyethylene fiber substrate, 6 parts of a fluorocarbon polymer layer, 10 parts of a resin layer, 3 parts of a nano-titanium dioxide photocatalyst, 1.2 parts of a photocatalyst auxiliary component, 5 parts of a super-hydrophobic coating, 0.5 parts of a self-assembled monolayer film, and 2.1 parts of a cross-linking agent.
[0073] The embodiment also provides a method for preparing a sunshade net with a self-cleaning function, comprising the following steps:
[0074] S1: Select polyethylene fiber as the substrate, roughen the fiber surface, use low-temperature plasma technology, the gas composition is argon and oxygen mixed, the ratio is Ar: O2 = 4: 1, the processing time is 50 seconds, the power is set to 180W, and the micron to nanometer level concave and convex structure is etched on the fiber surface;
[0075] S2: A thin layer of silane coupling agent is deposited on the roughened surface of the polyethylene fiber substrate by chemical vapor deposition. The deposition temperature is set to 100°C, the deposition time is 13 minutes, and the concentration of the silane coupling agent is controlled at 8%. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the polyethylene fiber to form a covalent bond, and the other end has a reactive functional group, which provides an active site for the firm bonding of the subsequent coating.
[0076] S3: A layer of fluorocarbon polymer solution is evenly coated on the surface of the functionalized fiber by solution dipping method. The concentration of the fluorocarbon polymer solution is 4%. The dipping time is 4 minutes, and then it is dried at 90°C for 14 minutes to ensure that the coating is uniform and firm.
[0077] S4: On the fluorocarbon polymer layer, a resin layer was deposited by electrostatic spraying technology. The viscosity of the resin solution was adjusted to 80 mPa·s, the spraying voltage was set to 40 kV, the spraying distance was maintained at 18 cm, and after deposition, it was cured at 140°C for 18 minutes;
[0078] S5: Nano-titanium dioxide particles were synthesized by sol-gel method and uniformly dispersed in aqueous solvent by ultrasonic dispersion technology. The concentration of nano-titanium dioxide particles was adjusted to 2% and the ultrasonic dispersion time was 50 minutes. Subsequently, the nano-titanium dioxide sol was coated on the resin layer by spin coating. The spin coating speed was set to 700 rpm and the spin coating time was 55 seconds. The distribution density and uniformity of the nano-particles on the fiber surface were controlled. Finally, heat treatment was performed at high temperature to make the nano-titanium dioxide particles firmly bonded to the fiber surface. The heat treatment temperature was 480°C and the duration was 2 hours. A crystal structure with high photocatalytic activity was formed.
[0079] S6: On the nano-titanium dioxide photocatalyst layer, a super-hydrophobic coating is constructed. First, a layer of low surface energy material is modified on the surface of the nano-titanium dioxide. The low surface energy material is fluorosilane. The concentration of the fluorosilane solution is 0.3%. Then, a dense self-assembled monolayer film is formed on the surface by self-assembly technology. The self-assembly time is 2 hours and the temperature is controlled at 25°C.
[0080] S7: adding a cross-linking agent, which forms covalent bonds or ionic bonds between the coatings through chemical reactions. The concentration of the cross-linking agent is controlled at 2%, the reaction temperature is set at 60°C, and the reaction time is 3 hours, thereby firmly locking the entire coating system together;
[0081] S8: After completing all the above coating construction, dry it naturally at room temperature or use an oven to dry it at 70°C for 45 minutes to ensure that the sunshade net is completely dry and has no residue, thereby obtaining a sunshade net with a self-cleaning function.
[0082] Embodiment 4
[0083] A sunshade net with a self-cleaning function comprises the following components in parts by weight: 60 parts of a polyethylene fiber substrate, 7 parts of a fluorocarbon polymer layer, 12 parts of a resin layer, 4 parts of a nano-titanium dioxide photocatalyst, 1.5 parts of a photocatalyst auxiliary component, 7 parts of a super-hydrophobic coating, 0.7 parts of a self-assembled monolayer film, and 2.5 parts of a cross-linking agent.
[0084] The embodiment also provides a method for preparing a sunshade net with a self-cleaning function, comprising the following steps:
[0085] S1: Select polyethylene fiber as the substrate, roughen the fiber surface, use low-temperature plasma technology, the gas composition is argon and oxygen mixed, the ratio is Ar: O2 = 4: 1, the processing time is 60 seconds, the power is set to 200W, and the micron to nanometer level concave-convex structure is etched on the fiber surface;
[0086] S2: A thin layer of silane coupling agent is deposited on the roughened surface of the polyethylene fiber substrate by chemical vapor deposition. The deposition temperature is set to 120°C, the deposition time is 15 minutes, and the concentration of the silane coupling agent is controlled at 10%. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the polyethylene fiber to form a covalent bond, and the other end has a reactive functional group, which provides an active site for the firm bonding of the subsequent coating:
[0087] S3: A layer of fluorocarbon polymer solution is evenly coated on the surface of the functionalized fiber by solution dipping method. The concentration of the fluorocarbon polymer solution is 5%. The dipping time is 5 minutes, and then it is dried at 100°C for 15 minutes to ensure that the coating is uniform and firm.
[0088] S4: On the fluorocarbon polymer layer, a resin layer is deposited by electrostatic spraying technology. The viscosity of the resin solution is adjusted to 100 mPa·s, the spraying voltage is set to 50 kV, the spraying distance is maintained at 20 cm, and after deposition, it is cured at 150°C for 20 minutes;
[0089] S5: Nano-titanium dioxide particles were synthesized by sol-gel method and uniformly dispersed in aqueous solvent by ultrasonic dispersion technology. The concentration of nano-titanium dioxide particles was adjusted to 3% and the ultrasonic dispersion time was 60 minutes. Subsequently, the nano-titanium dioxide sol was coated on the resin layer by spin coating. The spin coating speed was set to 1000 rpm and the spin coating time was 60 seconds. The distribution density and uniformity of the nano-particles on the fiber surface were controlled. Finally, heat treatment was performed at high temperature to make the nano-titanium dioxide particles firmly bonded to the fiber surface. The heat treatment temperature was 500°C and the duration was 2 hours. A crystal structure with high photocatalytic activity was formed.
[0090] S6: On top of the nano-titanium dioxide photocatalyst layer, a super-hydrophobic coating is constructed. First, a layer of low surface energy material is modified on the surface of the nano-titanium dioxide. The low surface energy material is fluorosilane, and the concentration of the fluorosilane solution is 0.5%. Then, a dense self-assembled monolayer film is formed on its surface by self-assembly technology. The self-assembly time is 2 hours, and the temperature is controlled at 30°C:
[0091] S7: adding a cross-linking agent, which forms covalent bonds or ionic bonds between the coatings through chemical reactions. The concentration of the cross-linking agent is controlled at 3%, the reaction temperature is set at 70°C, and the reaction time is 4 hours, thereby firmly locking the entire coating system together;
[0092] S8: After completing all the above coating construction, dry it naturally at room temperature or use an oven to dry it at 80°C for 60 minutes to ensure that the sunshade net is completely dry and has no residue, thereby obtaining a sunshade net with a self-cleaning function.
[0093] Embodiment 5
[0094] A sunshade net with a self-cleaning function and a preparation method thereof, on the basis that other conditions are the same, in S1 of the preparation method:
[0095] The concave-convex structure is designed to be corrugated. On the basis of the concave-convex structure, a papillary structure similar to the surface of a lotus leaf is formed on the fiber surface through chemical etching or physical deposition methods.
[0096] Example: Preparation of corrugated concave-convex structure and papillary structure
[0097] Improvements of S1 step:
[0098] Preparation of corrugated concave-convex structure:
[0099] Polyethylene fiber was selected as the base material.
[0100] The roughening process is performed using low-temperature plasma technology, and the gas composition is a mixture of argon and oxygen in a ratio of Ar:02=4:1.
[0101] The processing time was adjusted to 90 seconds (30 seconds longer than that of the fourth embodiment to better form the corrugated structure), and the power was set to 200W.
[0102] During the plasma treatment, the airflow speed and direction are controlled, and the distribution of plasma is adjusted to form a uniform corrugated concave-convex structure on the fiber surface. The period of the corrugation is set to 50 μm and the depth is 2 μm.
[0103] Preparation of papillary structures:
[0104] After the corrugated concave-convex structure is formed, the surface structure is further refined by chemical etching. The etching solution is a diluted hydrofluoric acid solution (HF concentration is controlled at 5%), and the etching time is 30 seconds.
[0105] Alternatively, a physical deposition method, such as sputtering deposition or vapor deposition, is used to deposit a thin layer of metal oxide (such as aluminum oxide AI203) on the surface of the corrugated concave-convex structure with a deposition thickness of 100 nm to form a papillary structure similar to the surface of a lotus leaf.
[0106] Whether chemical etching or physical deposition, the processing time and conditions need to be precisely controlled to ensure the uniformity and stability of the papillary structure.
[0107] Next steps:
[0108] The subsequent coating deposition and curing treatment are carried out according to steps S2 to S8 of Example 4.
[0109] Specific data:
[0110] Corrugated concave-convex structure: period 50μm, depth 2μm.
[0111] Papillary structure: If chemical etching is used, the HF concentration is 5% and the etching time is 30 seconds; if physical deposition is used, the deposition thickness is 100 nm.
[0112] Plasma treatment time: 90 seconds (30 seconds longer than Example 4).
[0113] The parameters and data in the remaining steps remain the same as those in Example 4.
[0114] Comparative Example 1
[0115] A sunshade net with a self-cleaning function and a preparation method thereof are basically the same as those of the fourth embodiment, except that the nano titanium dioxide photocatalyst and the photocatalyst auxiliary components are removed.
[0116] Comparative Example 2
[0117] A sunshade net with a self-cleaning function and a preparation method thereof are basically the same as the fourth embodiment, except that the super-hydrophobic coating and the self-assembled monolayer are removed.
[0118] Comparative Example 3
[0119] A sunshade net with a self-cleaning function and a preparation method thereof are basically the same as the fourth embodiment, except that the preparation steps are simplified and S2 (deposition of a silane coupling agent layer) and S7 (addition of a cross-linking agent) are omitted.
[0120] Comparative Example 4
[0121] A sunshade net with a self-cleaning function and a preparation method thereof are basically the same as the fourth embodiment, except that the thickness of the fluorocarbon polymer layer and the resin layer are reduced (i.e., their weight fractions are reduced).
[0122] The sunshade nets prepared in the above-mentioned embodiments 1 to 5 and comparative examples 1 to 4 were tested:
[0123] National standard testing standards:
[0124] GB / T 32313-2015 "Sunshade Net": This standard specifies the materials, specifications, performance requirements, test methods, etc. of sunshade nets. Although it does not directly mention the self-cleaning function, it is an important standard for evaluating the basic quality of sunshade nets.
[0125] Coating performance standards:
[0126] Related coating or surface treatment standards: Although there is no direct national standard for self-cleaning coatings for sunshade nets, you can refer to the coating performance standards in the fields of architectural coatings, functional films, etc., such as coating adhesion, weather resistance, photocatalytic activity, etc.
[0127] Specific detection method
[0128] Detection method:
[0129] Coating Adhesion Test: Use the cross-hatch method or pull-off method to test the adhesion between the coating and the substrate.
[0130] Weather resistance test: Place the sunshade net samples under simulated natural environmental conditions (such as ultraviolet radiation, high and low temperature cycles, rain, etc.) to observe the stability and self-cleaning effect of the coating.
[0131] Photocatalytic activity test: For coatings containing photocatalysts, use an ultraviolet light source to irradiate the sample and evaluate its photocatalytic activity by detecting the decomposition rate of organic matter on the sample surface.
[0132] Self-cleaning effect evaluation: Through simulated pollution experiments (such as spraying dust, oil, etc.), observe the cleaning effect of the surface of the sunshade net under natural conditions or artificial assistance (such as rain washing).
[0133] The results are shown in Table 1:
[0134] Table 1
[0135]
[0136]
[0137] From Table 1 above, it can be directly obtained that the coating adhesion of Examples 1 to 4 all reached Grade 5B, which indicates that in these Examples, the bonding between the coating and the substrate is very strong and can meet higher usage requirements.
[0138] In terms of weather resistance, Examples 1 to 4 all showed "no significant change". This means that under the aging test conditions, the performance of these sunshade nets remained stable without significant degradation or damage. This is very important for the long-term application of sunshade nets in outdoor environments.
[0139] In terms of photocatalytic activity, Examples 1 to 4 all achieved a 90% organic matter decomposition rate (within 24 hours), which indicates that these sunshade nets have efficient photocatalytic performance and can effectively decompose organic matter attached to their surfaces, thereby keeping them clean.
[0140] Regarding the self-cleaning effect, the first to fourth embodiments are nearly completely clean after being washed by rainwater, which means that under the action of rainwater, the stains on the surface of the sunshade net can be effectively washed away, thereby keeping it clean and beautiful.
[0141] From the data of Examples 1 to 4, these sunshade nets have excellent performance in coating adhesion, weather resistance, photocatalytic activity and self-cleaning effect. They have strong coating bonding, stable performance, efficient photocatalytic decomposition ability and good self-cleaning effect. These characteristics make these sunshade nets have a wide range of application prospects in outdoor environments, especially in occasions that need to be kept clean and beautiful for a long time.
[0142] In Example 5, where other conditions are the same, Example 5 designs the concave-convex structure into a corrugated shape. On the basis of the concave-convex structure, a papillary structure similar to the surface of a lotus leaf is formed on the fiber surface by chemical etching or physical deposition. After the final test, regarding the self-cleaning effect, Example 4 is close to completely clean after being washed by rainwater, while Example 5 is completely clean after being washed by rainwater. This is the only significant difference between the two examples. The self-cleaning effect of Example 5 is slightly better, and its surface structure or coating formula is more optimized in promoting stain washing.
[0143] Comparative Example 1 removes the nano-titanium dioxide photocatalyst and the photocatalyst auxiliary component. Due to the removal of the photocatalyst, the photocatalytic activity of Comparative Example 1 is significantly reduced (data not given, but can be inferred), and the self-cleaning effect will also be affected, because the photocatalyst is one of the key components for decomposing organic matter and achieving self-cleaning. From the data provided, Comparative Example 1 leaves a small amount of stains, which confirms the importance of the photocatalyst.
[0144] Comparative Example 2 removes the super-hydrophobic coating and the self-assembled monolayer film, which are crucial to improving the self-cleaning performance of the sunshade net. After removing these components, the self-cleaning effect of Comparative Example 2 will be significantly reduced. The data show that a small amount of stains remain in Comparative Example 2, indicating that its self-cleaning ability is not as good as that of Example 4.
[0145] Comparative Example 3 simplifies the preparation steps, omitting S2 (silane coupling agent layer deposition) and S7 (crosslinking agent addition). The silane coupling agent layer deposition and the addition of the crosslinking agent are essential for improving the adhesion and stability of the coating. After omitting these steps, the coating adhesion of Comparative Example 3 will be reduced, and the weather resistance may also be affected. From the data, the coating adhesion of Comparative Example 3 is not as good as that of Example 4 (although the data is not directly given), and the self-cleaning effect is poor, leaving more stains.
[0146] Comparative Example 4 reduces the thickness of the fluorocarbon polymer layer and the resin layer (i.e., reduces their weight fractions). The fluorocarbon polymer layer and the resin layer have an important influence on the weather resistance, self-cleaning effect and other properties of the sunshade net. Reducing the thickness of these layers will weaken the performance of the sunshade net. However, judging from the data, the performance of Comparative Example 4 has not decreased significantly, its photocatalytic activity remains at a high level (85% organic matter decomposition rate / 24h), and the self-cleaning effect is also close to complete cleaning. This shows that reducing the thickness of the fluorocarbon polymer layer and the resin layer within a certain range has little effect on the performance of the sunshade net.
[0147] From the comparison between Example 4 and Comparative Examples 1 to 4, it can be seen that each component and preparation step has an important influence on the performance of the sunshade net. Removing or simplifying key components and steps will lead to a decrease in the performance of the sunshade net, especially in terms of self-cleaning effect and photocatalytic activity. Therefore, when preparing a sunshade net with a self-cleaning function, it is necessary to comprehensively consider various factors to ensure that each component and step is effectively implemented.
[0148] The present invention realizes the efficient self-cleaning function of the sunshade net through the synergistic effect of multi-layer coatings and the specific surface structure design. The main components include a polyethylene fiber substrate, a fluorocarbon polymer layer, a resin layer, a nano-titanium dioxide photocatalyst, a photocatalyst auxiliary component, a super-hydrophobic coating, a self-assembled monolayer film and a cross-linking agent. Through the finely controlled preparation steps, such as low-temperature plasma treatment, chemical vapor deposition, solution impregnation, electrostatic spraying, sol-gel method, etc., the uniformity and firm bonding of each coating are ensured.
[0149] The surface structure design has been improved, and the concave-convex structure has been designed into a corrugated shape. On this basis, a papillary structure similar to the surface of a lotus leaf is formed through chemical etching or physical deposition methods, which significantly improves the self-cleaning effect of the sunshade net.
[0150] Nano-titanium dioxide photocatalysts can efficiently decompose organic matter attached to the surface of the sunshade net under light conditions, reducing the accumulation of pollutants. The combination of super-hydrophobic coating and self-assembled monolayer film allows water droplets to form water beads on the surface of the sunshade net and roll off quickly, effectively taking away dust and dirt. The combination of corrugated concave-convex structure and papillary structure further enhances the self-cleaning ability of the sunshade net, making the rainwater flushing effect better.
[0151] The fluorocarbon polymer layer and the resin layer have excellent weather resistance, which can keep the performance of the sunshade net stable under various climatic conditions. The strong bond between the coatings prevents the coating from peeling off or cracking due to environmental changes.
[0152] The use of silane coupling agent layer strengthens the bonding between the coating and the substrate, ensuring the long-term stability of the coating. The addition of cross-linking agent further consolidates the connection between the coatings and improves the overall durability.
[0153] The use of photocatalysts reduces the need for chemical cleaning agents, which is beneficial to environmental protection. The self-cleaning function reduces the frequency of manual cleaning, saving water resources and energy.
[0154] The sunshade net is suitable for various outdoor environments, such as agricultural greenhouses, outdoor leisure facilities, etc., and can keep clean and beautiful for a long time. Its excellent performance characteristics make it have unique advantages in occasions that require high cleanliness requirements.
[0155] In summary, the present invention realizes the efficient self-cleaning function of the sunshade net through the synergistic effect of multi-layer coatings and fine surface structure design, and has excellent weather resistance, coating adhesion and broad application prospects. It provides strong technical support for the application of sunshade nets in outdoor environments and has important practical value and economic significance.
[0156] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A sunshade net with self-cleaning function, characterized in that: The invention comprises the following components in parts by weight: 40 to 60 parts of a polyethylene fiber substrate, 3 to 7 parts of a fluorocarbon polymer layer, 8 to 12 parts of a resin layer, 2 to 4 parts of a nano titanium dioxide photocatalyst, 0.5 to 1.5 parts of a photocatalyst auxiliary component, 3 to 7 parts of a super-hydrophobic coating, 0.3 to 0.7 parts of a self-assembled monolayer film, and 1.5 to 2.5 parts of a cross-linking agent.
2. The sunshade net with self-cleaning function according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 50 parts of polyethylene fiber substrate, 6 parts of fluorocarbon polymer layer, 9 parts of resin layer, 4 parts of nano titanium dioxide photocatalyst, 0.8 parts of photocatalyst auxiliary component, 5 parts of super hydrophobic coating, 0.6 parts of self-assembled monolayer film and 1.9 parts of cross-linking agent.
3. A sunshade net with self-cleaning function according to claim 1 or 2, characterized in that: The fiber diameter of the polyethylene fiber substrate is 0.2 mm to 0.5 mm, the surface of the polyethylene fiber substrate is subjected to corona treatment or plasma treatment, the fluorocarbon polymer layer uses polyvinylidene fluoride (PVDF) as the main fluorocarbon polymer component, the thickness is 5 μm to 15 μm, the fluorocarbon polymer layer has a micro-nano rough structure, the super hydrophobic coating is composed of fluorosilane and silicon dioxide with a rough structure, the resin layer uses modified silicone resin, the thickness is 3 μm to 8 μm, the resin layer is used as an intermediate layer to connect the substrate and the functional coating, the self-assembled monolayer film uses molecules with carboxyl groups, and an ordered monolayer film is formed on the surface of the substrate through self-assembly technology, the thickness of the self-assembled monolayer film is 1 nm to 5 nm, and the cross-linking agent is an epoxy resin cross-linking agent.
4. A sunshade net with self-cleaning function according to claim 1 or 2, characterized in that: The nano titanium dioxide photocatalyst adopts anatase nano titanium dioxide with a particle size of 10nm to 30nm. The contact angle of the nano titanium dioxide photocatalyst with water is greater than 150°, and the rolling angle is less than 10°. It is prepared by a sol-gel method. The photocatalyst auxiliary components include sodium citrate and sodium acetate. The molar ratio of sodium citrate to soluble zinc salt is 1:10 to 3:20, and the molar ratio of sodium acetate to soluble zinc salt is 25:10 to 40:
20.
5. The sunshade net with self-cleaning function according to claim 1, characterized in that: The surface of the polyethylene fiber substrate is designed with a nanometer-level concavo-convex structure, which helps to form a super-hydrophobic surface. When rain falls on the sunshade net, it can quickly form water droplets and roll down, taking away dust and dirt on the surface, and / or the surface of the polyethylene fiber substrate is designed to simulate the wax layer and papillary structure of the lotus leaf surface to form a micro-nano structure of a self-cleaning surface; The fluorocarbon polymer is combined with nanoparticles having super hydrophobicity to form a nanocomposite coating, which not only has the low surface energy characteristics of the fluorocarbon polymer, but also has enhanced super hydrophobicity due to the rough structure of the nanoparticles; An ordered self-assembled monolayer is formed on the surface of the fluorocarbon polymer layer by chemical methods. The self-assembled monolayer can adjust the surface energy and improve the binding force with nanoparticles. The nano titanium dioxide photocatalyst uses a one-dimensional or two-dimensional titanium dioxide nanostructure as a photocatalyst, and the titanium dioxide is doped and modified by adding nitrogen and sulfur elements to broaden its light absorption range and improve its photocatalytic activity under visible light.
6. A method for preparing a sunshade net with a self-cleaning function according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Select polyethylene fiber as the substrate, roughen the fiber surface, and use low-temperature plasma technology to etch micron to nanometer-scale concave-convex structures on the fiber surface by adjusting the gas composition and treatment time; S2: A thin layer of silane coupling agent is deposited on the roughened surface of the polyethylene fiber substrate by chemical vapor deposition. One end of the silane coupling agent reacts with the hydroxyl group on the surface of the polyethylene fiber to form a covalent bond, and the other end carries a reactive functional group, providing an active site for the firm bonding of the subsequent coating. S3: A layer of fluorocarbon polymer solution is uniformly coated on the functionalized fiber surface by solution dipping method; S4: depositing a resin layer on the fluorocarbon polymer layer using an electrostatic spraying technique; S5: Nano-titanium dioxide particles are synthesized by sol-gel method and uniformly dispersed in aqueous solvent by ultrasonic dispersion technology. Subsequently, the nano-titanium dioxide sol is coated on the resin layer by spin coating. During the spin coating process, the distribution density and uniformity of the nano-particles on the fiber surface are controlled by adjusting the rotation speed and time. Finally, heat treatment is performed at high temperature to make the nano-titanium dioxide particles firmly bonded to the fiber surface and form a crystal structure with high photocatalytic activity. S6: On top of the nano-titanium dioxide photocatalyst layer, a super-hydrophobic coating is constructed. First, a layer of low surface energy material is modified on the surface of the nano-titanium dioxide, and then a dense self-assembled monolayer film is formed on its surface by self-assembly technology; S7: adding a cross-linking agent, which forms covalent bonds or ionic bonds between the coatings through chemical reactions, thereby firmly locking the entire coating system together; S8: After all the above coatings are constructed, the sunshade net is fully cleaned and dried to obtain a sunshade net with a self-cleaning function.
7. The method for preparing a sunshade net with a self-cleaning function according to claim 6, characterized in that: In S1, polyethylene fiber is selected as the substrate, and the fiber surface is roughened by using low-temperature plasma technology. The gas composition is a mixture of argon and oxygen in a ratio of Ar:02=4:
1. The processing time is 30 to 60 seconds, and the power is set to 100 to 200 W. A micron to nanometer level concave-convex structure is etched on the fiber surface.
8. The method for preparing a sunshade net with a self-cleaning function according to claim 6, characterized in that: In S1, the concave-convex structure is designed to be corrugated, and on the basis of the concave-convex structure, a papillary structure similar to the surface of a lotus leaf is formed on the fiber surface by chemical etching or physical deposition method.
9. The method for preparing a sunshade net with a self-cleaning function according to claim 6, characterized in that: In S5, nano titanium dioxide particles are synthesized by a sol-gel method, and are uniformly dispersed in an aqueous solvent by ultrasonic dispersion technology. The concentration of the nano titanium dioxide particles is adjusted to 1% to 3%, and the ultrasonic dispersion time is 30 to 60 minutes. Subsequently, the nano titanium dioxide sol is coated on the resin layer by spin coating, and the spin coating speed is set to 500 to 1000 rpm for 30 to 60 seconds to control the distribution density and uniformity of the nano particles on the fiber surface. Finally, heat treatment is performed at a high temperature to firmly bond the nano titanium dioxide particles to the fiber surface. The heat treatment temperature is 400 to 500° C. for 1 to 2 hours to form a crystal structure with high photocatalytic activity.
10. The method for preparing a sunshade net with a self-cleaning function according to claim 6, characterized in that: In the S6, a super hydrophobic coating is constructed on the nano titanium dioxide photocatalyst layer. First, a layer of low surface energy material is modified on the surface of the nano titanium dioxide. The low surface energy material is fluorosilane, and the concentration of the fluorosilane solution is 0.1% to 0.5%. Then, a dense self-assembled monolayer film is formed on its surface through self-assembly technology. The self-assembly time is 1 to 2 hours, and the temperature is controlled at 20 to 30°C.
Citation Information
Cited By
Degradable plastic with self-cleaning function and preparation method thereof
CN121779796A